CONTRIBUTION OF GUIDANCE AND COUNSELING SUPERVISION TOWARD COUNSELOR PERFORMANCE: STUDY IN SUMATERA UTARA - Sandjaja, Stefanus Soejanto; Syahputra, Yuda; Hariyani, Hariyani (Guidance and Counseling Study Program, Pattimura University, 2020)
The purpose of this study is to illustrate the contribution of BK supervision to counselor performance. The sample of this study was 87 Counselor spread in Sumatera Utara schools. Data were collected through two questionnaires, namely: BK supervision (reliability item 0.91) and the performance of Counselor (reliability item 0.95), which was analyzed descriptively. The results showed that the counselor performance was in the good category with a percentage of 62.1% and the supervision of the BK received was in the good category with a percentage of 50.6%. Furthermore, the results of the study indicate there is a contribution to the supervision of BK on the performance of Counselor with a contribution value of 20.2%. Besides that, the regression coefficient is positive, so it can be stated that the influence of the BK supervision variable (X) on the counselor performance (Y) teacher is positive. The implications are further discussed for the supervisory process of the counselor performance